Existing Governance Structures for Sustainable Solid Waste Management in Kisii Town, Kenya. - Naftal, Mecheo Omonywa; Mutua, Dr. Bessy Kathambi; Moronge, Dr. James M. (Diponegoro University, 2023)
Solid waste management (SWM) is a major challenge in many urban areas in developing countries. The governance structures in the management of solid wastes are overwhelmed to sustainably manage them. This study sought to assess the governance structures for sustainable solid waste management in Kisii town. Study was anchored on the zero -waste theory and the circular economy theory. The study engaged a cross-sectional research design. The sample size was derived from the sampling formula of Yamane. Data collection methods encompassed questionnaires and interview schedules using a mobile software of KOBO for administration of questionnaires. Data from interviews was analyzed using both descriptive and inferential analysis; data from the questionnaires was coded and analyzed using softwares as KOBO, SPSS and excel. The results indicate that: there exist governance structures in SWM in Kisii town known at 45% by the residents, there are both national and county laws, policies and regulations. The most popular structures are; EMCA regulation to the residents is on-source separation at 78.3%, polluter pay principle at 20.3% and colour code separation the least 15%. Of the NEMA laws; EPR is known to the respondents at 67.1%, waste reuse and recycle 30% and waste valorization (2021) not common at 21.6%. The respondents are not aware of the existing county by-laws; only 46.7% are aware of the on-source separation policy. In conclusion, there exist governance structures; guided by the national EMCA 1999 laws, NEMA policies and regulations and Kisii county by-laws and policies. The resident’s knowledge concerning the existing laws and policies is limited. Its therefore recommended that, Public participation should be incorporated in all decisions, laws, policy and regulation. Also, public education through the media, banners, posters, public baraza and other methods be carried out to sensitize the general public SWM governance structures.